Determinant of Individual Taxpayers’ Compliance in Banyuwangi Regency, Indonesia - Galih Wicaksono (Jurnal Riset Akuntansi Terpadu, 2022)
This study aims to determine the factors that influence the compliance of individual taxpayers in the Banyuwangi Regency, Indonesia. The population in this study was 74,361 taxpayers. Based on the calculation of the Slovin formula, the samples in this study were 100 people. The sampling technique uses proportional area random sampling, which is in 25 Sub-districts in Banyuwangi Regency, where each sub-district will be taken at least four respondents, so it is expected to photograph the level of tax compliance in Banyuwangi as a whole. This research uses quantitative methods by analyzing quantitative data on questionnaires to empirically prove the factors that influence the level of compliance of individual taxpayers. This study results in the finding that partially, only the variable understanding of regulations has a significant effect on taxpayer compliance. This means that if the taxpayer has a good understanding of tax regulations, it will increase taxpayer compliance. Conversely, if understanding tax regulations are low, it will reduce the level of compliance. Partially, the variables of the role of awareness, understanding of regulations, service quality, and tax sanctions together have a significant effect on taxpayer compliance, amounting to 52.2%.